Pharmacognostic and antidiabetic study of Clitoria ternatea - Manish Gunjan,; Ravindran M,; Sengamalam R,; Goutam K Jana,; A.K Jha, (International Journal of Phytomedicine, 2010)
Aparajita means "The Undefeated". This plant is a trailing creeper with the usual Indigo Blue colour flowers and the rare white ones which is more of a pale cream with a hint of green at the edges. In Kerala it is called the Sankhu Pushpam or Conch Shell flower although it hardly resembles a Conch shell. It actually resembles a quaint Snapdragon flower with it's front open. Graphically it represents the cutout of an inverted womb. May be that explains their close affinity to Indian Midwives, particularly the White variety. Aparajita grows throughout India. It is a beautiful-looking plant, hence cultivated in gardens. It is a perennial twining herb having 7 leaflets, which are elliptic and obtuse. There are few varieties with white, violet and blue flowers. The pods are 5-7 cm long, flat with 6 to 10 seed, in each pod. The flowers resemble in shape to cows ear, hence the synonym- gokarnika. Chronic administration of plant extracts (100mg/kg) for 14 days reduces the blood glucose level of the diabetes induced animals as compared to diabetic control group. There was significant decrease in the blood glucose level in the 7th [p<0.01] and 14th [p<0.001] days of the diabetes induction, showing antidiabetic effect. The effect was comparable to that of standard antidiabetic drug Glibenclamide. The aim of this research is to explore the antidiabetic activity of this plant which will be helpful in the future investigations.